Organic-Aggregate-Attached Bacteria in Aquatic Ecosystems: Abundance, Diversity, Community Dynamics and Function - Tang, Xiangming; Chao, Jianying; Chen, Dan; Shao, Keqiang; Gao, Guang (IntechOpen, 2012)
None